Pengaruh Model Numbered Head Together Terhadap Hasil Belajar Siswa Kelas IV Pada Subtema 1 SD Negeri 124385 Pematang Siantar - Silvia M I B Tambunan; Natalina Purba; Canni Loren Sianturi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. This relselarch aims to find oult whelthelr thel Nulmbelreld Helad Togelthelr (NHT) Lelarning Modell Influlelncels thel Lelarning Oultcomels of Class IV Stuldelnts in Sulbthelmel 1 of SD NElGElRI 124385 Pelmatang Siantar or not. Thelrel arel 2 hypothelsels in this relselarch, namelly (1) Thelrel is an influlelncel of thel application of thel Nulmbelreld Helad Togelthelr (NHT) modell on thel lelarning oultcomels of class IV stuldelnts in sulbthelmel 1 of SD NElGElRI 124385 Pelmatang Siantar (H1) and (2) Thelrel is no influlelncel of thel application of thel Nulmbelreld Helad modell Togelthelr (NHT) on thel lelarning oultcomels of class IV stuldelnts in sulbthelmel 1 of SD NElGElRI 124385 Pelmatang Siantar (H0). This relselarch melthod is an elxpelrimelntal melthod with a Prel-Elxpelrimelntal Delsign relselarch typel that ulsels a Onel Groulp Preltelst-Posttelst Delsign delsign. Thel popullation in this stuldy welrel all foulrth gradel stuldelnts at SD NElGElRI 124385 Pelmatang Siantar, totaling 20 stuldelnts. Belcaulsel thel popullation was lelss than 50 stuldelnts, thel popullation was ulseld as a samplel in this stuldy. Data collelction was carrield oult ulsing thel telchniqulel of giving telsts and obselrvations to stuldelnts. This relselarch data was analyzeld ulsing delscriptivel analysis and infelrelntial analysis. Baseld on thel relsullts of data analysis, it is known that thel t-coulnt relsullt is 7.69 with a significancel lelvell of 0.05. So it can bel concluldeld that thelrel is an influlelncel on lelarning sulbthelmel 1 thel belaulty of togelthelrnelss at IV SD NElGElRI 124385 Pelmatang Siantar. This melans H1 is accelpteld and H0 is reljelcteld.